HUBUNGAN DUKUNGAN SOSIAL TEMAN SEBAYA DENGAN EFIKASI DIRI MAHASISWA UMN AL-WASHLIYAH SEBAGAI CALON GURU BK - Tria Yulita; Ika Sandra Dewi; Nurul Azmi Saragih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to determine whether peer social support is related to self-efficacy among BK UMN Al-Washliyah students who are preparing to become teachers. A total of 32 active students were selected as samples for this study. Data analysis was conducted using Pearson's correlation, while data was collected using a Likert scale. The results of the study found that peer social support was significantly associated with students' self-efficacy (r=0.463 and p<0.05). These findings confirm that a supportive social environment, particularly in the form of peer support, plays a role in shaping students' self-confidence, motivation, and professional readiness, and contributes to the design of guidance and counselling programmes that pay greater attention to students' social aspects.